A The Role Of Iot In Improving Security And Real-Time Monitoring At PT Pelindo Regional 1 - Amin, Muhammad (Cattleya Darmaya Fortuna, 2024)
The role of the Internet of Things (IoT) is increasingly important in improving security and real-time monitoring in the port industry. PT Pelindo Regional 1, as one of the major port operators in Indonesia, faces huge challenges in managing ship traffic, goods flow, and infrastructure security. The application of IoT technology can provide solutions to improve operational efficiency, strengthen security systems, and enable real-time monitoring of various port assets and processes. Through connected sensors and advanced analytics systems, IoT helps detect potential security threats early, optimize the use of resources, and minimize the risk of loss. This study explores how the implementation of IoT at PT Pelindo Regional 1 has impacted the improvement of the security system and provides a more detailed view of the benefits of real-time monitoring in maintaining smooth port operations.